High‐resolution coral oxygen and carbon isotope records reveal temperature and autotrophy dynamics in a Mediterranean climate change hotspot - Diego K. Kersting; Thomas C. Brachert; Juan P. D'Olivo; Cristina Linares; Lars Reuning; Joan Lluís Riera; Philipp Spreter; Ulrich Struck; Marina J. Vergotti; Jens Zinke (Limnology and Oceanography, 2025)
The Mediterranean Sea is warming at a rate exceeding the global average. Long‐term, high‐resolution data are essential for contextualizing changes within broader temporal scales, and coral skeletons provide valuable environmental archives, especially in data‐sparse regions or as supplements to existing records. While coral‐based reconstructions are well established in tropical settings, they remain limited in temperate areas. As the only reef‐building zooxanthellate coral in the Mediterranean, Cladocora caespitosa is particularly important for expanding coral‐based environmental archives in these understudied regions. Here, we present records of δ 18 O and δ 13 C in the skeletons of C. caespitosa from a global change sentinel site in NW Mediterranean. This study provides the most accurate temperature–δ 18 O calibration equations for C. caespitosa , including a traditional linear model and a novel exponential model that better accounts for the region's wide seasonal temperature range. Both calibrations rely on long‐term in situ water temperature data and a multi‐corallite composite approach to reduce non‐climatic variability. Seasonal trends in δ 13 C reveal, for the first time, variation in the coral's autotrophy–heterotrophy balance, while geochemical anomalies in the skeletons signal thermal stress effects on biomineralization. Our findings establish C. caespitosa skeletons as critical archives for reconstructing anthropogenic warming and its ecological effects in the Mediterranean.

Effects of climate change on marine coastal ecosystems – A review to guide research and management - Ewan Trégarot; Juan Pablo D'Olivo; Andrea Zita Botelho; Andrea Cabrito; Gabriel O. Cardoso; Gema Casal; Cindy C. Cornet; Simon M. Cragg; A. Karima Degia; Stein Fredriksen; Elisa Furlan; Georg Heiss; et al. (Biological Conservation, 2024)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Rolling corals in the Mediterranean Sea - D. K. Kersting; E. Cebrian; J. Verdura; E. Ballesteros (Coral Reefs, 2017)

A new Cladocora caespitosa population with unique ecological traits - D. KERSTING; E. CEBRIAN; J. VERDURA; E. BALLESTEROS (Mediterranean Marine Science, 2017)
The Mediterranean endemic scleractinian coral Cladocora caespitosa (L., 1767) has been recently included in the IUCN Red List as an endangered species. In this context, information on the species is urgently required to further assess its status and to determine its distribution area. This study reports on the main traits of a recently discovered C. caespitosa population in Formentera (Balearic Islands, W Mediterranean). Here, coral colonies live wrapped in Cystoseira forests thriving on rocky substrata (5 - 13 m depth), thus being a new example of the ability of C. caespitosa to build up extensive populations within algal communities. Even though coral cover reaches ~ 20 % on average, which is a remarkable figure for this species, colonies are generally small (~ 10 cm diameter on average), most probably due to partial exposure to waves and currents. The combination of hydrodynamics and the presence of algal forests in the studied site could be responsible for the high occurrence of a rare type of colony growth: free-living coral nodules or coralliths. This population is highly interesting for future monitoring owing to its unique traits, the absence of necrosis signs related to past mortality events, and its location inside a marine reserve.

Diseases of coralline algae in the Mediterranean Sea - B. Hereu; D. K. Kersting (Coral Reefs, 2016)

Recruitment patterns in the Mediterranean deep-water alga Cystoseira zosteroides - P. Capdevila; C. Linares; E. Aspillaga; L. Navarro; D. K. Kersting; B. Hereu (Marine Biology, 2015)

Harmonisation of food categorisation systems for dietary exposure assessments among European children - M. De Neve; I. Sioen; P.E. Boon; C. Arganini; J. Moschandreas; J. Ruprich; L. Lafay; P. Amiano; D. Arcella; M. Azpiri; L. Busk; T. Christensen; et al. (Food Additives & Contaminants: Part A, 2010)

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

The measurement of ingestion of phytoplankton by zooplankton: Techniques, problems and recommendations - C. Bakker; R. D. Gulati; K. Kersting (Aquatic Ecology, 1985)